A Step Towads Modernism: Serov and the Post Impressionist Movements in European Art - Malycheva, Tanja (Actual Problems of Theory and History of Art, 2013)
While in Venice in 1887 Serov saw not only the Venetian Old masters who brought a primacy of colour over line, he also visited the Esposizione nazionale artistica — the exhibition that preceded the Biennale — that had on display over 1700 works by contemporary artists, with Sargent and Segantini among them. In this context Serov’s portraits of Vera Mamontova (1887) and Maria Simonovich (1888) will be re-evaluated, discussing the role of Venice in the development of modernistic tendencies and postimpressionistic movements in Europe and relating to the image of Italy in Russian art of 19th century.
Keywords: Serov; Italy; Venice; Mamontova; Simonovich; Sargent; Segantini; Rossi; Raphael; Italian genre